2019
DOI: 10.1186/s12894-019-0568-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of case volume per year on flexible Ureteroscopy practice: an internet based survey

Abstract: BackgroundTo report current worldwide variation in techniques and clinical practice of flexible ureteroscopy (FURS) among endourologists of different case volumes per year.MethodsTwo invitations to complete an internet survey were emailed to Endourological Society members. Some of survey questions asked about indications of using FURS for renal and upper ureteral stones. Others were concerned with clinical practice of FURS (such as preoperative stenting, use of ureteral access sheath (UAS) and safety guidewire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Complications were significantly lower with experienced surgeon in comparison with non-experienced surgeons ( p = 0.001) [ 9 ]. Moreover, experienced surgeons tend to perform FURS for larger stones [ 11 ]. Frontczak et al performed propensity score-matched retrospective study and found that stone-free status for large renal stones (>20 mm) was significantly better with experienced surgeons [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complications were significantly lower with experienced surgeon in comparison with non-experienced surgeons ( p = 0.001) [ 9 ]. Moreover, experienced surgeons tend to perform FURS for larger stones [ 11 ]. Frontczak et al performed propensity score-matched retrospective study and found that stone-free status for large renal stones (>20 mm) was significantly better with experienced surgeons [ 12 ].…”
Section: Discussionmentioning
confidence: 99%